Histological and prognostic importance of CD44+/CD24+/EpCAM+ expression in clinical pancreatic cancer. Issue 8 (24th June 2013) - Ohara, Yusuke; Oda, Tatsuya; Sugano, Masato; Hashimoto, Shinji; Enomoto, Tsuyoshi; Yamada, Keiichi; Akashi, Yoshimasa; Miyamoto, Ryoichi; Kobayashi, Akihiko; Fukunaga, Kiyoshi; Morishita, Yukio; Ohkohchi, Nobuhiro
Abstract : CD44 + /CD24 + /EpCAM + cells have been reported to be cancer stem cells in pancreatic cancer; however, the histological and clinical importance of these cells has not yet been investigated. Here we clarified the characteristics of CD44 + /CD24 + /EpCAM + cells in clinical specimens of pancreatic cancer using immunohistochemical assay. We used surgical specimens of pancreatic ductal adenocarcinoma from 101 patients. In view of tumor heterogeneity, we randomly selected 10 high‐power fields per case, and triple‐positive CD44 + /CD24 + /EpCAM + expression was identified using our scoring system. The distribution, histological characteristics, and prognostic importance of CD44 + /CD24 + /EpCAM + cells were then analyzed. As a result, the distribution of CD44 + /CD24 + /EpCAM + cells varied widely among the 101 cases examined, and CD44 + /CD24 + /EpCAM + expression was correlated with poor glandular differentiation and high proliferation. Survival analysis showed that CD44 + /CD24 + /EpCAM + expression was not correlated with patient outcome; however, CD44 + /CD24 + expression appeared to be correlated with poor prognosis. In conclusion, CD44 + /CD24 + /EpCAM + expression overlapped with poorly differentiated cells and possessed high proliferative potential in clinical pancreatic cancer. In particular, the presence of double‐positive CD44 + /CD24 + expression seemed to have clinical relevance, associating with poor prognosis.